Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0164852
|View full text |Cite
|
Sign up to set email alerts
|

Association of Types of Life Events with Depressive Symptoms among Puerto Rican Youth

Abstract: The main objective of this study was to examine the association between four types of adverse life events (family environment, separation, social adversity, and death) and the development of depressive symptoms among Puerto Rican youth. This was a secondary analysis using three waves (2000–2004) of interview data from the Boricua Youth Study of 10–13 year old Puerto Rican youth residing in New York and Puerto Rico with no depressive symptoms at baseline (n = 977). Depressive symptoms increased with an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 86 publications
(89 reference statements)
1
20
0
Order By: Relevance
“…Consistent with previous studies that have indicated a positive association between adversity exposure and depressive symptoms among Mexican and Latino adolescents (Benjet et al, 2019; Jaschek et al, 2016), we found that higher levels of adversity were linked to a greater likelihood of experiencing MDD and MDE in one’s lifetime and the past year. However, we did not observe significant interactions between depression PRS and adversity with phenotypic MDD or MDE.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies that have indicated a positive association between adversity exposure and depressive symptoms among Mexican and Latino adolescents (Benjet et al, 2019; Jaschek et al, 2016), we found that higher levels of adversity were linked to a greater likelihood of experiencing MDD and MDE in one’s lifetime and the past year. However, we did not observe significant interactions between depression PRS and adversity with phenotypic MDD or MDE.…”
Section: Discussionsupporting
confidence: 91%
“…One well-documented environmental contributor to depression is adverse life events (Llabre et al, 2017). For example, experiencing adversity (i.e., sexual abuse, having a parent with depression, family disruption) during childhood or adolescence has been associated with a depression diagnosis among Mexican (Benjet et al, 2019) and Latino adolescents (Jaschek et al, 2016). Moreover, exposure to adversity may profoundly shape the developing brain and neurobiological systems that make some individuals more sensitive to future stressors (McIlwricka et al, 2016;Starr et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…number of coworkers who died) increased the likelihood of screening positively for MDD symptoms, consistent with prior studies. 24,27,28 Furthermore, knowing one or more coworkers hospitalized or in the ICU was significantly associated with screening positively for GAD symptoms, suggesting that the experience of having colleagues fall ill may intensify anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the cultural expectation of familism, familial relationships were often strained due to incarceration, familial dysfunction, arguments, and parental abandonment (Crist et al 2009;Flores et al 2009;Jaschek et al 2016;Kreling et al 2010). As this woman shared about her own mother, "Yeah, she didn't want me, so my grandma did.…”
Section: Caregiving Is Women's Workmentioning
confidence: 99%